Removal of Chromium from Wastewater using Activated Eggshells - Kenishan, Yakeshwaran (Universiti Teknologi PETRONAS, 2016)
This project paper presents the results of experiment carried out on sorption of Cr (III) ions from chromium solution by eggshells as a low cost sorbent. The eggshell in a powdered form is a potentially beneficial option for the removal of toxic chromium from industrial wastewater. The principal component of the shell is calcium carbonate which comprises more than 90% of the carbon material. Crushed eggshells possess relatively high sorption capacity, when comparing with other sorbents. The effect of process parameters: contact time, sorbent dosage, pH, and temperature, initial concentration of Cr (III) ions on the process was studied. Sample eggshells collected washed thoroughly using sodium hydroxide solution and deionized water. The eggshells were then dried at 110°C in an oven and crushed accordingly and later stored in quick-fit glass bottles for further use.